Acquired persistent self-healing Langerhans cell histiocytosis. - Demirci, G.T.; Altunay, I.K.; Ates, B.; Demiralay, E. (European Journal of Pediatric Dermatology, 2011)
The classification of Langerhans cell histiocytosis (LCH) includes single-system disease involving a single site, single-system disease affecting multiple sites and multisystem disease. Self-healing reticulo-histiocytosis (SHRH) or Hashimoto-Pritzker disease is an obsolete term regarding congenital, pure cutaneous, self-healing Langerhans cell histiocytosis. A 2-year-old infant referred to our clinic with multiple brownish-red pruritic papulonodules on left axilla and trunk started at the age of 2 months. The histopathological examination of the skin biopsy revealed a dense infiltrate of histiocytic cells with kidney-like nuclei and foamy eosinophilic cytoplasm in the superficial and deep dermis. Immunohistochemistry demostrated that most infiltrating cells were positive for S-100 protein and CD1a. Systemic examination of the child revealed no abnormalities. Six months later the cutaneous lesions disappeared. Two years after the resolution of the lesions the child was symptom-free with no signs of relapse or systemic involvement. The final diagnosis was acquired pure cutaneous self-healing Langerhans cell histiocytosis.